A Critical Analysis of Various Welfare Programs and Activities Organized By Maharashtra Labour Welfare Board: Promoting the well-being and development of workers through welfare programs in Maharashtra (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Maharashtra State is a leading state in India, which is implementingthe Labour Welfare Scheme, out of the workplace for the benefit of workers andtheir families. In 1938 then Mumbai State Government started a first Labour WelfareCentre at Delisle Road, presently known as N. M. Joshi Marg. The welfarefacilities were made available in the locality where the workers were residingin majority, with an aim to motivate workers to desist from the addictions likealcohol, tobacco and gambling. It was also aimed at to encourage spending theirleisure time in a proper manner and in a constructive way. It was also intendedthat workers shall avail an opportunity to develop themselves socially andculturally. These Welfare Centres were intended to start libraries, indoor andoutdoor games and entertainment programs.